Fit Assessment of Safety Helmets among Female Engineering Students in UTHM Pagoh Campus - Nurul Athirah Sharudin; Mustafa El Bakri, Helmy (Progress in Engineering Application and Technology, 2026)
Wearing personal protective equipment (PPE) is essential to ensure the health and safety of workers and personnel at work. Safety helmets are an essential component of personal protective equipment (PPE) designed to reduce the risk of head injuries caused by falling objects, collisions, and other occupational hazards. However, many safety helmets that are sold commercially don’t suit all user demographics well, especially among female users. This study evaluates the global and local Helmet Fit Index (HFI) of standard safety helmets worn by female engineering students at Universiti Tun Hussein Onn Malaysia (UTHM), Pagoh Campus. 3D scanning and post-processing techniques in Geomagic were used to capture and analyse the geometric relationship between the head and helmet’s inner surface. A total of thirty participants were involved. Global HFI and local HFI values for five head regions (front, top, left, right, and back) were determined based on standoff distance (SOD), gap uniformity (GU), and head protection proportion (HPP) that interpreted by using CATIA. The results indicate that the overall helmet fit is relatively low, with very low Global Helmet Fit Index (HFI) values and large negative standoff distances, particularly at the top and front regions, where the widest gaps and poorest gap uniformity were observed, while the left, right, and back regions exhibited comparatively smaller gaps and better conformity to the head shape. These findings highlight the limitations of current helmet designs in accommodating female head morphology and provide valuable input for future helmet design improvements.